Research based on the method of Android system active defense without Root permission - Jing-qiang LIU; Bin LI; Li-zhang CHEN; Bin CHEN (网络与信息安全学报)
In order to solve the problem that the system security is reduced through getting Root permission and that the security of Android smartphone is not effective without Root permission, the working principle of ART, the Java reflection mechanism and AOP principle were studied. The new mechanism was designed and implemented to avoid the security problem caused by the traditional protection application of Hooking system function in the kernel layer and the limitations with calling API in the application layer ineffectively. The interception of sensitive behavior and the protection of smartphone were both achieved.